2003
DOI: 10.1074/jbc.m302977200
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Integrity of the Serpin Domain of C1-inhibitor Depends on the Unique N-terminal Domain, as Revealed by a Pathological Mutant

Abstract: C1-inhibitor (C1-InhThe autosomal dominant disease hereditary angioedema (HAE) 1 is caused by functional deficiency of C1-inhibitor (C1-Inh) (1). C1-Inh is the major inhibitor of C1s and C1r of the classical pathway of complement and also an inhibitor of the contact system proteases, factor XIIa, kallikrein, and factor XIa (2-9). A lack of this inhibitor may result in recurrent episodes of acute, local, circumscribed edema of the skin or mucosa. The most serious and potentially life-threatening manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…The expression yields ranged from 3-10 mg/l and, therefore, were comparable to that reported previously for the production of full-length C1 inhibitor using the same expression system (16). In keeping with the report by Wolff et al (16) and in contrast with the highly heterogeneous material produced in P. pastoris (12,19), the C1 inhibitor serpin domain expressed in the current study was homogeneous in terms of size, as shown by SDS-PAGE and MALDI mass spectrometry analyses, indicating relative homogeneity of the N-linked oligosaccharides. In this regard, the mass spectrometry analyses performed on the recombinant proteins are consistent with the occurrence of short, oligomannose carbohydrates comprising two N-acetylglucosamine residues and three to four mannose residues (calculated mass = 893-1055), in keeping with previous analyses (16).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The expression yields ranged from 3-10 mg/l and, therefore, were comparable to that reported previously for the production of full-length C1 inhibitor using the same expression system (16). In keeping with the report by Wolff et al (16) and in contrast with the highly heterogeneous material produced in P. pastoris (12,19), the C1 inhibitor serpin domain expressed in the current study was homogeneous in terms of size, as shown by SDS-PAGE and MALDI mass spectrometry analyses, indicating relative homogeneity of the N-linked oligosaccharides. In this regard, the mass spectrometry analyses performed on the recombinant proteins are consistent with the occurrence of short, oligomannose carbohydrates comprising two N-acetylglucosamine residues and three to four mannose residues (calculated mass = 893-1055), in keeping with previous analyses (16).…”
Section: Discussionsupporting
confidence: 88%
“…1). The N-terminal extension of C1 inhibitor does not seem to affect protease inhibition (11,12), and its functional role remains elusive. However, interaction of C1 inhibitor with selectins on endothelial cells is known to be mediated by tetrasaccharides located in this area (9).…”
mentioning
confidence: 99%
“…This truncation removes the nonconserved part of C1-inh and leaves most of the biological activities essentially unchanged (11,12) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing analysis revealed 14 potential O-glycosylation sites (9), seven of which had been verified by carbohydrate analysis (10). Most of the sugars are present in the N-terminal domain and do not affect proteinase inhibition (11,12), but affinity to endotoxins and selectins depends on the N-glycans.…”
mentioning
confidence: 99%
“…Also, a part of the C1-INH amino acid sequence of Asp 84 to Thr 138 corresponded to the sequence that is lost in patients with C1-INH deficiency (Fig. 3C) (23). The second cleavage site between Val 127 and Thr 128 was also included in the sequence.…”
Section: Streptococcal Cysteine Protease Speb Degrades Human C1mentioning
confidence: 83%